Math, asked by rupakdey567p5ujr8, 1 year ago

(8a³/27x-³)⅔ * (64a³/27x-³)-⅔

Answers

Answered by johnkumarrr4
17

1/4

Step-by-step explanation:

given expression

=\left ( 8\times a^{3}/\left ( 27\times x^{-3} \right ) \right )^{2/3}\times \left ( 64\times a^{3} /\left ( 27\times x^{-3} \right )\right )^{-2/3}

=\left ( 2\times a\times x/3 \right )^{3\times 2/3}\times \left ( 4\times a\times x/3 \right )^{3\times( -2/3)\}

=\left ( 2/3\times a\times x \right )^{2}\times \left ( 4/3\times a\times x \right )^{-2}

=\left ( 2/3\times a\times x \right )^{2}\times \left ( 3/\left ( 4\times a\times x \right ) \right )^{2}

=2^{2}\times a^{2}\times x^{2}/3^{2}\times 3^{2}/(4^{2}\times a^{2}\times x^{2})

cancel the term which is present in numerator and denominator a,x,3

=2^{2}/4^{2}

=\left ( 2/4 \right )^{2}

=\left ( 1/2 \right )^{2}

=1/4

Answered by anamikasinghoptical7
5

Here is your answer

Attachments:
Similar questions